The Influence of Welding Technique With Variation of Current on Surface Defects and Penetration of ST40 Steel - M. Hidayatur Rokhim; Mulyadi (Journal for Technology and Science, 2024)
One of the connection of one place starting from several materials or materials that are solid is one of the welding methods, as for the factors that can affect the quality of the weld results which include the process of tools and materials to be used, welding direction, welding electrode movement patterns, in order to use and select electrodes. In this study ST 40 steel plate, testing was carried out with 3 specimens using U and zigzag movement patterns and the direction of welding used back and forth. variations in electric current used are 40 A, 60 A, 80 A. This study has the aim of influencing welding techniques using current variations. The test results that the welding process using welding techniques consisting of movement patterns, welding direction and welding time does not affect the weld defects in the welding results. Welds defects that occur due to variations in the current used